Simple and Easily Connectable Transition from Empty Substrate-Integrated Waveguide to a 3D Printed Rectangular Waveguide - Darío Herraiz; Angel Belenguer; Marcos Fernandez; Santiago Cogollos; Héctor Esteban; Vicente E. Boria (Applied Sciences, 2023)
3D printing is one of the most promising manufacturing methods in the most developed technological fields, including microwave hardware fabrication. On the other hand, the well-known manufacturing methods of planar substrate integrated circuits allow high-quality prototypes to be made at low cost and with mass production capabilities. The combination of both manufacturing methods, 2D or 2.5D (substrate integrated circuits) and 3D (3D printed structures), will allow us to take advantage of the main strengths of each technology and minimise disadvantages. In this article, for the first time, a transition structure between the Empty Substrate-Integrated Waveguide (ESIW) technology—a planar waveguide integrated on a printed circuit board—and a standard rectangular waveguide manufactured by 3D printing is proposed. This transition will make it possible to combine planar circuits with 3D structures, thus taking advantage of the benefits of both types of technologies. The fabricated prototype presents low losses (0.6 dB for the transmission coefficient and 15 dB for reflection coefficient), good electrical response (very flat), and simultaneously good mechanical stability and robustness to manufacturing and assembly errors. The proposed design for this transition piece is easily realisable for a wide range of affordable 3D printers. Repeatability is guaranteed and the proposed transition allows us to combine different SIC structures to 3D printed circuits. Hence, this transition will enable advancements in the fabrication of microwave devices, particularly with regard to satellite communications.